Pengaruh Model Pembelajaran Course Review Horray (CRH) Terhadap Keaktifan Belajar PAK Siswa Kelas X SMK Swasta Yapim Balige Kabupaten Toba Tahun Pembelajaran 2022/2023 - Martina Labora Nainggolan; Dorlan Naibaho; Maria Widiastuti (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
The aim of this research is to determine the influence of the Course Review Horray (CRH) learning model on the active learning of Christian Religious Education of class The method used in this research is descriptive quantitative. The population is all class Data was collected using a positive closed questionnaire of 40 items, of which 20 questionnaire items were for variable class X Yapim Balige Private Vocational School, Toba Regency, 2022/2023 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.580 > rtable(a=0.05,n=45) = 0.294, thus it is known that there is a positive relationship between variable X and variable Y. b) Test A significant relationship is obtained by the value of tcount= 4.667 > ttable(a=0.05,dk=n-2=43)= 2.021, thus there is a significant relationship between variable X and variable Y. 2) Test the effect: a) Test the regression equation , the regression equation Y ̂="36.86"+0.44X is obtained. b) Regression coefficient of determination test (r2) = 33.6%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=20, dk denominator=n-2=45-2=43) namely 21.69 > 1.51. Thus Ha is accepted and H0 is rejected. Keywords: Learning Model, Course Review Horray (CRH) Model, Learning Activeness, PAK